Acute symptomatic seizures and status epilepticus in older adults: A narrative review focusing on management and outcomes - Kong, Wan Yee; Marawar, Rohit (Frontiers in Neurology, 2022)
A clear narrative of acute symptomatic seizures (ASyS) in older adults is lacking. Older adults (≥60 years) have the highest incidence of seizures of all age groups and necessitate a tailored approach. ASyS has a bimodal peak in infancy and old age (82.3–123.2/100,000/year after 65 years of age). ASyS can represent half of the new-onset seizures in older adults and can progress to acute symptomatic status epilepticus (ASySE) in 52–72% of the patients. Common etiologies for ASyS in older adults include acute stroke and metabolic disturbances. For ASySE, common etiologies are acute stroke and anoxic brain injury (ABI). Initial testing for ASyS should be consistent with the most common and urgent etiologies. A 20-min electroencephalogram (EEG) is less sensitive in older adults than in younger adults and might not help predict chronic epilepsy. The prolonged postictal phase is an additional challenge for acute management. Studies note that 30% of older adults with ASyS subsequently develop epilepsy. The risk of wrongly equating ASyS as the first seizure of epilepsy is higher in older adults due to the increased long-term challenges with chronic anti-seizure medication (ASM) treatment. Specific challenges to managing ASyS in older adults are related to their chronic comorbidities and polypharmacy. It is unclear if the prognosis of ASyS is dependent on the underlying etiology. Short-term mortality is 1.6 to 3.6 times higher than younger adults. ASySE has high short-term mortality, especially when it is secondary to acute stroke. An acute symptomatic etiology of ASySE had five times increased risk of short-term mortality compared to other types of etiology.